Sound transmission loss of a sandwich functionally graded cylindrical shell integrated with magneto-electro-elastic patches. (20th January 2023) - Abdolhoseyni, J.; Danesh, M.
Highlights: At below the f r, flow Mach number has no significant effect on STL. To improve the acoustic insulation performance, a greater magnetic and electric potentials can be utilized. With increasing FG index, a lower STL value is observed at the beginning of frequency region. With increasing the curvature angle and number of MEE patches, STL increases slightly. Abstract: Magneto-electro-elastic materials offers the inherent capability of energy transformation from one type to another, hence making them suitable for improving the vibroacoustic behavior of the structures. The current article is an analytical investigation into the sound transmission characteristics of a smart functionally graded cylindrical shell equipped with magneto-electro-elastic patches while a steady fluid flow exists outside of the cylinder. The complete set of equations of motion are derived after accounting for all components of displacement according to the first-order shear deformation theory. The utilized patches are controlled via an electric field, indicating the smart nature of the structure. The Power-law model is adopted to calculate the effective mechanical properties of the functionally graded core layer. After defining proper boundary conditions, the vibroacoustic equations are obtained with the aid of Hamilton's principle. A comprehensive validation study is also conducted to show the reliability of the developed formulation. In addition, by examining the effect of a large number of electric, magnetic, flow Mach number, geometric and acoustic parameters, recommendations are made to effectively optimize similar structures that benefit from such materials. One of the important findings of this study is that applying electric and magnetic fields in the low frequency band improves the sound transmission loss. Therefore, the magneto-electro-elastic patches can be used in active structural acoustic control approaches as actuators.